2013
DOI: 10.5539/jas.v5n9p83
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Selection Behaviors and Chemical Cues of adult Asian Citrus Psyllids, Diaphorina citri, on Healthy and Huanglongbing-Infected Young Shoots of Citrus Plants

Abstract: The pathogen Candidatus Liberibacter asiaticus (Las) causes devastating citrus huanglongbing in many parts of Asia. The host selection behavior of the Asian citrus psyllid, Diaphorina citri Kuwayama (Hemiptera: Sternorrhyncha: Psyllidae), the only known Las vector, is critical to its epidemics. Las-infected citrus plants attract adult psyllids by altering their color and chemical cues. However, it is unclear whether any changes in selection behavior or chemical cues occur in young shoots. Selection behavior bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 33 publications
0
5
0
3
Order By: Relevance
“…Zhao et al . () revealed that significantly higher populations of eggs and adults were found in Las‐infected shoots than Las‐free shoots of citrus, suggesting that the odours of Las‐infected shoots are more attractive to citrus psyllid than uninfected shoots. Wu et al .…”
Section: Discussionmentioning
confidence: 99%
“…Zhao et al . () revealed that significantly higher populations of eggs and adults were found in Las‐infected shoots than Las‐free shoots of citrus, suggesting that the odours of Las‐infected shoots are more attractive to citrus psyllid than uninfected shoots. Wu et al .…”
Section: Discussionmentioning
confidence: 99%
“…ACP responded differently to the odour emitted by its host plants. When the host trees were infected by Candidatus Liberibacter asiaticus ( C Las), the number of adults and eggs on symptomatic shoots was significantly higher than on non‐symptomatic shoots . Although C Las‐infected plants were initially more attractive to ACP adults than were non‐infected plants, the non‐infected healthy plants were preferred settling points for the dispersing psyllids after being contracted with HLB bacteria from feeding on diseased trees .…”
Section: Psyllid Attractant Researchmentioning
confidence: 99%
“…Tabela 1 -Lista dos compostos químicos encontrados nos extratos de voláteis de plantas de citros sadias e plantas de citros sintomáticas para HLB a Identificação feita pela co-injeção de composto sintético padrão b % em relação a área total dos compostos do tratamento TR = Tempo de reteção; KI = Índice de Kovats; Teste-'t' de Student (*P ≤ 0,05; ** P ≤ 0,01) -CEVALLOS et al, 2011;MANN et al, 2012;ZHAO et al, 2013; HIJAZ; EL-SHESHENY; KILLINY, 2013), os resultados do presente trabalho a primeira evidência experimental de alterações químicas ocorridas em plantas de C. sinensis 'Pêra' enxertada sobre 'limão cravo', que é a principal variedade cítrica dos pomares brasileiros (PIO et al, 2005).…”
Section: Análise Química E Comparação Dos Perfis De Voláteis De Plantunclassified
“…Para avançar nestes conhecimentos, a resposta comportamental de adultos de D. citri vem sendo investigada frente aos voláteis de diferentes espécies de plantas, fornecendo subsídios importantes para compreensão dos fatores envolvidos nestas interações. Utilizando olfatômetros 'Y', trabalhos recentes demonstraram a resposta olfativa de D. citri para odores de murta e de diferentes espécies de citros (WENNINGER; STELINSKI;HALL, 2009;NORONHA Jr., 2010;SÉTAMOU, 2010;MANN et al, 2012;ZHAO et al, 2013). De acordo com trabalho deWenninger, Stelinski e Hall (2009), machos e fêmeas de psilídeos respondem diferentemente aos mesmos estímulos olfativos, e suas respostas variam para diferentes espécies de plantas hospedeiras.…”
unclassified
See 1 more Smart Citation